Functional nanostructred photoanodes for solar fuel production - Mohamed, Ahmad Mohyeldin (AUC Knowledge Fountain, 2015)
Improving the efficiency of water splitting process is one of the main obstacles that are facing the generation of renewable energy. Charge carriers separation is always coupled with low visible light absorption and stability of the materials used. Various efforts have been done in order to construct a full system of different materials that can absorb visible light efficiently, with an enhanced electron hole separation process for an efficient water splitting. However, most of the reported systems suffer either from crystal mismatch between the multiple materials the use of long linkers that promote the recombination of the carriers. In this thesis, we are introduce a new system of titania nanotubes that are functionalized with graphene quantum dot, as a photosensitizer and an efficient charge carrier collector and transporter. In the first part of the thesis, one-dimensional TiO2 nanotubes photoanodes were investigated. We are able to produce ultra thin walled titania nanotubes, for the first time. Thin walled titania nanotubes showed higher quantum efficiency; about 50% compared to 15 % for conventional thick-walled nanotubes, with a 50% enhancement in the photocurrent. This enhancement is mainly attributed to the very small wall thickness (3 nm), allowing the diffusion of the charge carriers across the wall, regardless the potential across the region. In the second part, the effect of hydrogen annealing on the optical and electrical properties of the thin-walled nanotubes was investigated. It was found hydrogen annealing for 4 hours passivate the trap states on the surface of titania, while annealing for longer times acts to create more defect states, larger carrier concentration, larger dark current, higher resistance. In addition, we introduced a new concept by adding KOH and hydrogen annealing resulted in lower resistance and higher charge carrier concentration and photocurrent. In the third part, we produced graphene quantum dots, and for the first time, we were able to functionalize graphene quantum dots with different groups (mercapto propanoic acid, and malonyl group). We also introduced a new anchoring method for graphene quantum dots on the surface of titania. The photocurrent was enhanced by 50%, and the reasons were discussed in details. Finally, we showed the possible new applications for titania nanotubes that are functionalized with our graphene quantum dots.